Corporate Social Responsibility Is A Mechanism For Strengthening Environmental Management Systems - Nacera YAHIAOUI; Mahdi MOURAD (Social Sciences Journal, 2019)
The social responsibility of the most important concepts exchanged between financiers and business around the world and highlights the importance of this proposal, as has been done to include the role played by companies in the field of sustainable development , and the indecisive burden an essential task in economic development, which is reflected directly on the social level. Several academic studies have shown the importance of harnessing social responsibility in business organizations as a tool to support environmental management systems and achieve sustainable development. And it's no longer in the organization's interest, either in the long run or the short-neglected aspects of environmental protection and various environmental resources, since the adoption of environmental management systems. the environment has become necessary to ensure that the continuity of institutions and improve its economic performance and as well as maintaining its image in the ocean that you are